MOTIVASI DAN PERSEPSI KONSUMEN PENGGUNA LAPTOP MEREK ACER (Studi Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Musamus Merauke) - Muhammad Awal (Universitas Musamus,Merauke,Papua, 2018)
This research was conducted to see the effect of motivation & perception of the decision to use the Acer brand laptop on students of the Faculty of Economics and Business, Musamus Merauke University. The population in this study was 1116 of the total number of FEB students. The sample in the study was 92 respondents with the sampling method accidental porposife sampling. The technique used is multiple linear regression. From the test results, the t test & F test show that the motivation & perception variables have a positive effect, are significant partially, or simultaneously towards the decision to use the Acer brand laptop on FEB students at Musamus Merauke University.